Digital Financial Literacy and Financial Inclusion: Visualizing Knowledge Networks through Bibliometric Analysis - Irma Kurniasari (Universitas Muhammadiyah Makassar, 2025)
This study examines the intersection of digital financial literacy and financial inclusion by employing a bibliometric approach to map global research trends, key contributors, and thematic developments in the field. Data were retrieved from the Scopus database, covering publications from 2012 to 2025, and analyzed using Biblioshiny in the R environment. Results reveal a substantial increase in research activity after 2018, reflecting growing academic and policy attention to the role of digital literacy in advancing inclusive finance. India, the United States, and China emerge as the most active contributors, highlighting the global relevance of this issue across both developed and developing economies. Thematic mapping identifies financial literacy, digital financial services, education, empowerment, and fintech adoption as central topics driving the discourse. Network analyses further demonstrate strong international collaborations and an evolving research structure that connects digital technologies, financial behavior, and socio-economic development. Despite these advances, challenges remain in bridging the digital divide, particularly for marginalized groups with limited access to technological infrastructure and financial education. This study contributes by providing a comprehensive overview of the knowledge network on digital financial literacy and inclusion, offering insights for policymakers, educators, and researchers. Strengthening digital financial competencies, supported by inclusive policies and collaborative scholarship, is critical for ensuring equitable access to safe and sustainable financial services in the digital era.